2022
DOI: 10.11591/ijere.v11i4.22081
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity of the organizational health inventory among Omani teachers: Invariance across gender

Abstract: <span lang="EN-US">This study examined the factor structure of the Organizational Health Inventory (OHI) scale among Omani teachers. There were four factors assumed to represent the OHI (principal influence, academic emphasis, morale, and initiating integrity). Testing the scale reliability was another aim of this study. A random sample (n=458) of Omani teachers was considered. The short version of the scale has 30 items. Exploratory and confirmatory factor analysis was performed on the sample data. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Confirmatory factor analysis indicated that the Omani version of Career Futures Inventory (CFIO-24) had comparable construct validity to the original CFI-25, especially after deletion of item 8 to improve model fit (CMIN/DF = 1.65, TLI=0.89, CFI= 0.91, RMSRE=0.06). Results indicated good confidence in using the CFIO-24 scale to estimate the level of career adaptability, optimism, and perceived career knowledge of undergraduate students in Oman (Abu Shindi et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Confirmatory factor analysis indicated that the Omani version of Career Futures Inventory (CFIO-24) had comparable construct validity to the original CFI-25, especially after deletion of item 8 to improve model fit (CMIN/DF = 1.65, TLI=0.89, CFI= 0.91, RMSRE=0.06). Results indicated good confidence in using the CFIO-24 scale to estimate the level of career adaptability, optimism, and perceived career knowledge of undergraduate students in Oman (Abu Shindi et al, 2020).…”
Section: Discussionmentioning
confidence: 93%